Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.15421/021922
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic processes in the organism of animals under the action of plant extract

Abstract: The possibility of increasing metabolism and resistance in an organism of animals under the influence of biologically active substances of natural origin is considered in the paper. In the current study, we investigated the effect of 40% ethanolic extract of common nettle (Urtica dioica L.) on hematologic indexes (hemoglobin concentration, erythrocytes and leukocytes content), protein metabolism (total protein, aspartate aminotransferase (AST), alanine aminotransferase activities (ALT)), glutathione metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…It was found that the 40% ethanolic extract exhibits the highest radical scavenging activity and best reduces the formation of free radical products in an in vitro system (Buchko et al, 2016). In another study (Havryliak et al, 2019), the antioxidant activity of 40% ethanolic extract was confirmed by three methods, which are based on different abilities to reduce DPPH+ radicals, ABTS+, and Fe 3+ ions. As a result, we used this extract in our further studies for the correction of stressful conditions in animals, which are accompanied by a violation of the pro-oxidant-antioxidant balance.…”
Section: Introductionmentioning
confidence: 94%
“…It was found that the 40% ethanolic extract exhibits the highest radical scavenging activity and best reduces the formation of free radical products in an in vitro system (Buchko et al, 2016). In another study (Havryliak et al, 2019), the antioxidant activity of 40% ethanolic extract was confirmed by three methods, which are based on different abilities to reduce DPPH+ radicals, ABTS+, and Fe 3+ ions. As a result, we used this extract in our further studies for the correction of stressful conditions in animals, which are accompanied by a violation of the pro-oxidant-antioxidant balance.…”
Section: Introductionmentioning
confidence: 94%
“…These preparations can be used to increase the adaptability and correct metabolic disorders in animals and humans (Keleş et al, 2020;Grauso et al, 2020). In our previous study on laboratory animals, we reported stimulation of erythropoiesis, activation of protein metabolism, inhibition of free radical processes, and an increase in endogenous reserves of antioxidant protection in the blood and tissues of nettle extract-supplemented rats after adrenaline-induced stress (Buchko et al, 2019).…”
Section: Introductionmentioning
confidence: 95%